5-Ammoniumvaleric acid stabilized mixed-dimensional perovskite submicron platelets with white light emission. Issue 10 (7th September 2020) - Shi, Yamin; Hu, Jiarui; Chen, Jian; Xu, Yaxin; Yang, Wantian; Chen, Junnian; He, Yunbin
Abstract : Zwitterionic 5-ammoniumvaleric acid (5-AVA) was employed to synthesize mixed-dimensional AVA x (MAPbCl3 ) perovskite submicron platelets that exhibit structural dimensionality dependent broadband emission. Abstract : Low-dimensional Pb–Br and Pb–Cl perovskite single crystals have aroused considerable attention due to their broadband white-light emission. But their synthesis involving halogenation of organic amines, dissolution of lead oxide and a slow cooling process is quite complicated. Herein, we report white light emission from mixed-dimensional AVA x (MAPbCl3 ) perovskite submicron platelets formed by one-step solution processing. It is found that the presence of 5-ammoniumvaleric acid (5-AVA) with a zwitterionic functional group is crucial for modulating the morphology and structural dimensionality of perovskites. Importantly, AVA x (MAPbCl3 ) perovskites exhibit distinctive structural dimensionality dependent broadband emission, indicating the formation of self-trapped excited states. The AVA2 (MAPbCl3 ) perovskite exhibits white-light emission with a color rendering index (CRI) of 85 and a correlated color temperature (CCT) of 8624 K, yielding "cold" white light. Moreover, the mixed-dimensional perovskite exhibits good stability for more than 30 days. With this report, we aim to provide a facile approach for synthesizing stable low-dimensional perovskite nanostructures for making advanced optoelectronic devices.